VENTILATOR ASSOCIATED PNEUMONIA IN TRAUMA PATIENTS; ASSOCIATED RISK FACTORS, MICROBIAL ETIOLOGY AND OUTCOME - Manzoor, Sohaima; Batool, Farzana; Sayeed, Muneeba Ahsan; Dhiloo, Azizullah Khan; Ismail, Humera Muhammad; Baqi, Shehla (Pakistan Armed Forces Medical Journal, 2021)
Objective: To assess the incidence, risk factors and outcome of ventilator associated pneumonia in trauma patients. Study Design: Prospective observational study. Place and Duration of Study: Shaheed Mohtarma Benazir Bhutto Institute of Trauma, Karachi, from Jul to Dec 2019. Methodology: All trauma patients, above 12 years, placed on mechanical ventilation in the emergency room or intensive care unit, were enrolled. Patients that developed a clinical pulmonary infection score of less than 6 were diagnosed with ventilator associated pneumonia. Results: A total of 113 patients were enrolled in this study. Mean age was 32.9 ± 14.4 years. Thirty eight (33.6%) developed ventilator associated pneumonia. Patients with ventilator associated pneumonia, compared to non-ventilator associated pneumonia, had a longer emergency room stay of 7.8 ± 10.1 vs. 4.7 ± 7.4 days (p-value=0.013), greater ventilator days of 18.5 ± 12.6 vs. 7.9 ± 5.5 (p-value=0.001), longer hospital stay of >14 days in 65.8% vs. 33.3% (p-value=0.001) and higher mortality of 65.8% vs. 56% (p-value=0.213). Nurse to patient ratio and infection control measures for prevention of ventilator associated pneumonia were significantly reduced in emergency room compared to intensive care unit (p-value=0.001). Out of 43 respiratory isolates in 38 ventilator associated pneumonia patients, 40 (93%) were gram negatives of which 23 (57.5%) were multidrug resistant with polymyxins as the only therapeutic option. Conclusion: There was a high incidence of ventilator associated pneumonia in patients with trauma. Prolonged retention in the emergency room is a significant risk factor for ventilator associated pneumonia, due to understaffing..................